Penilaian Potensi Daya Tarik Wisata Kampung Hasta Karya Semarang - Salsabilla, Rosyifa Aura; Kurniati, Rina (Teknik PWK (Perencanaan Wilayah Kota), 2024)
An alternative for tourism development in Semarang city is developing potential thematic villages into tourist destinations. Hasta Karya village has the potential for a special interest tourist attraction. However, this tourist attraction has not been fully utilized, namely there are no supporting attractions and several tourist facilities such as public toilets, sewage treatment systems and public green open space. There is no support from CSR, lack of promotion and marketing, as well as community participation, especially youth. This study aims to determine the level of utilization of potential tourist attractions owned by Hasta Karya Village as a tourist destination and to formulate directions for utilizing its potential. The study used a quantitative approach with data collection techniques in the form of questionnaires, interviews, and field observations. The results of the analysis show that Hasta Karya Village has the potential for handicrafts with originality values that are able to attract tourists. This potential is utilized by developing the concept of special interest tourism in the form of educational tourism attractions and shopping. Based on the components of tourist attraction, namely attractions, amenities, accessibility, and additional services, Hasta Karya Village has high potential to become a new tourist destination. The analysis of IFAS and EFAS shows that the strategic position of the potential tourist attraction of Kampung Hasta Karya is in quadrant I which has the potential for Development of tourist destinations.